Research on optimal coil configuration scheme of insulator relay WPT system - Wang, Wei; Duan, Mingrong; Zeng, Zhenwei; Liu, Huai; Ji, Zhenya (Frontiers in Electronics, 2023)
With the rapid development of the smart grid, on-line monitoring devices in the transmission tower have been widely used. However, the power supply problem has become an important bottleneck in the development of transmission tower intelligent sensing technology. Hence, the multi-relay coils wireless power transfer technology has been proposed to supply for the tower monitoring equipment in this paper. The effects of the number, arrangement position and turns of relay coils on the performance of WPT system are further explored. The simulation results show that the operation performance of WPT can be significantly improved by optimizing the coil arrangement position and turns. Moreover, there are multiple configuration schemes that the design indexes of the system could be achieved. The experiment results show that in the 110kV high-voltage transmission with the insulator length of 1.015m, the transmitting power and efficiency of the WPT system could be increased to 1.81W and 60.11% respectively by parameters optimization, which ensures the continuous and stable work of the monitoring equipment.